2020
DOI: 10.3389/fonc.2020.01277
|View full text |Cite
|
Sign up to set email alerts
|

In situ Metabolic Profiling of Ovarian Cancer Tumor Xenografts: A Digital Pathology Approach

Abstract: Metabolic profiling of cancer is a rising interest in the field of biomarker development. One bottleneck of its clinical exploitation, however, is the lack of simple and quantitative techniques that enable to capture the key metabolic traits of tumor from archival samples. In fact, liquid chromatography associated with mass spectrometry is the gold-standard technique for the study of tumor metabolism because it has high levels of accuracy and precision. However, it requires freshly frozen samples, which are di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Therefore, the MCT4-dependent mechanisms that contribute to EOC relapse need to be elucidated, because this transporter can potentially be used in targeted therapy in drug-resistant OC. The study conducted on mice with OC revealed that elevated MCT4 concentration yielded increased mouse mortality [ 50 ]. Interestingly, enhanced expression of MCT4 was observed in tumor stroma, especially in cancer-associated fibroblasts in breast cancer, whereas MCT1 was preferentially expressed in epithelial cancer cells and contributed to the influx of lactate to cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the MCT4-dependent mechanisms that contribute to EOC relapse need to be elucidated, because this transporter can potentially be used in targeted therapy in drug-resistant OC. The study conducted on mice with OC revealed that elevated MCT4 concentration yielded increased mouse mortality [ 50 ]. Interestingly, enhanced expression of MCT4 was observed in tumor stroma, especially in cancer-associated fibroblasts in breast cancer, whereas MCT1 was preferentially expressed in epithelial cancer cells and contributed to the influx of lactate to cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, high PKM2 expression was closely associated with poor PFS, and correlated with short OS in platinum-treated epithelial ovarian cancer (23)(24)(25). For metabolite transporters, the expression level of GLUTs was not a prognostic factor of ovarian cancer, however, MCT4 negatively correlated with survival of mice confirmed based on in situ metabolic profiling of ovarian cancer tumor xenografts (26,27). However, the prognostic value of other indicators in ovarian cancer has not been extensively explored.…”
Section: Discussionmentioning
confidence: 99%
“…Aperio Cytoplasm V2 algorithm was used to analyse cytoplasmic positivity of TRPM7 expression, based on criteria for TRPM7 in human breast cancer. 29 , 30 The positive expression of TRPM7 in cytoplasm was quantitatively assessed, for each sample in 10 randomly selected high‐power fields (400×), as follows: 0 (negative), +1 (weakly positive), +2 (moderately positive) and + 3 (strongly positive). Staining intensities for TRPM7 expression ranged from 0 to 3 and were correlated with conventional manual scoring methods.…”
Section: Methodsmentioning
confidence: 99%